2015
DOI: 10.5114/kitp.2015.56784
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of anticoagulation with warfarin: experience of one cardiac centre

Abstract: IntroductionThe risk of complications in anticoagulation therapy can be reduced by maximising the percentage of time spent by the patient in the optimal therapeutic range (TTR). However, little is known about the predictors of anticoagulation control. The aim of this paper was to assess the quality of anticoagulant therapy in patients on warfarin and to identify the factors affecting its deterioration.Material and methodsWe studied 149 patients who required anticoagulant therapy with warfarin due to non-valvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
(35 reference statements)
0
15
1
1
Order By: Relevance
“…This result was consistent with the outcome of our study. Ciurus et al [11] examined 149 warfarin-treated patients in a cardiology clinic and showed that anticoagulation assessment was satisfactory and mean TTR was 76% ± 21%. Undas et al [12] demonstrated an improvement in anticoagulation quality in 68 patients by switching from acenocoumarol to warfarin and obtaining an increase in TTR from 40.2% to 60.4% during six months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was consistent with the outcome of our study. Ciurus et al [11] examined 149 warfarin-treated patients in a cardiology clinic and showed that anticoagulation assessment was satisfactory and mean TTR was 76% ± 21%. Undas et al [12] demonstrated an improvement in anticoagulation quality in 68 patients by switching from acenocoumarol to warfarin and obtaining an increase in TTR from 40.2% to 60.4% during six months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The key reason for carrying out this study was the lack of multi-centre studies carried out by general practitioners aimed at evaluating anticoagulation effectiveness in Polish urban and rural populations. Most of the publications so far pertained to specialist care [11,12] or to primary health care studies carried out in a single practice [13]. The aim of this study was to assess the therapeutic quality of oral anticoagulation and to determine factors that affect the incidence of INR outside the recommended range in primary care patients undergoing long-term VKA therapy in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…In ARISTOTLE study the mean TTR was 66% 21 , in RE-LY study 67.2%, with the highest values of 77% in Sweden and 74% in Finland and Australia 10,11 . On the other hand, Gateman D et al calculated the mean TTR in St. Paul Family Health Network in Ontario of 58.05% 8 , while the mean TTR in the study of Ciurus T et al is 76% that is considered to represent excellent anticoagulation control 1 . According to our study, the mean value of TTR is 60.15% during a follow-up of one year, and it is lower than that reported from big clinical trials, but still correlates with the number of the existing data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the implementation of new oral anticoagulants (NOAC) for the treatment of patients with atrial fibrillation or venous thromboembolism, vitamin K antagonists (VKA), such as warfarin, acenocoumarol and phenprocoumon are still the most widely used oral anticoagulants. The most common indications for their use are atrial fibrillation, mitral or aortic stenosis, mitral or aortic prosthetic valve, venous thromboembolism and intracavitary thrombosis 1,2 . This therapy is long lasting, for months and years, and in some cases till the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that comorbidities and the patient characteristics that affect the quality of warfarin therapy may vary among countries. [14][15][16] In a study from Unites States, Nelson et al 12 reported that HF, diabetes mellitus, and previous stroke were associated with a lower TTR in patients with NVAF, yet age did not associate with poor anticoagulation control. However, in the AF in Turkey: Epidemiologic registry, age was found to be the only independent factor of stroke in patients with NVAF 15 and VAF.…”
Section: Discussionmentioning
confidence: 99%